Algoritmo automático para la corrección del factor de potencia en redes industriales - Freire Rodríguez, Abel Eloy (2019)
In the industries, there are capacitor banks at the entrance of the electric power supply for POWER FACTOR CORRECTION according to the requirements of the energy supplier company. Then, the problem is found at the capacitor banks located in the power supply since they do not correct the technical losses downstream, within the industry, produced by the core-loss current. Knowing the most appropriate point to improve the power factor optimally can be obtained with the application of a computer tool that is fast and effective. That is why the software was designed in Matlab that allows improving the power factor in industrial networks. Through the software in Matlab, an algorithm was proposed which is based on the search for a cost reduction incurred by the industry, due to the aliquot of the electric service bill known as the demand charge, presented by the supplier company. This demand charge that is composed of a reactive fraction is part of the total demand billed; although it is not a useful power, it also represents a significant cost in the electricity service form. That is the reason why the researchers developed that computer tool with which they achieved the reduction and the most efficient location of capacitor banks into industrial networks.